Projeto e desenvolvimento de sistema de gestão de atendimento a pacientes em internação hospitalar - Quaranta, Thiago Cinelli (2019)
This work presents the development of a system to monitor the patient care in hospitals through RFID technology, in relation to the moments in which the consultations are requested and the moments in which these are initiated or finalized. The idea arose from the need to record the care given to hospitalized patients, since records made manually are more prone to errors. The development of the work consisted of two stages, the first being the study of the components used for the development of the system. The second was the practical development of the system, where the integration between components, RFID TAGs, RFID reader, Arduino, RS485 modules and a system-user interface were performed. The latter being an API between a C code and the Windows operating system spreadsheet program, Microsoft Office Excel. As a result, the system is expected to provide better records facilitating the management of hospital care.